Influenza virus M2 protein ion channel activity stabilizes the native form of fowl plague virus hemagglutinin during intracellular transport. - Takeuchi, K (1994)
The influenza A/fowl plague virus/Rostock/34 hemagglutinin (HA), which is cleaved intracellularly and has a high pH threshold (pH 5.9) for undergoing its conformational change to the low-pH form, was expressed from cDNA in CV-1 and HeLa T4 cells in the absence of other influenza virus proteins. It was found, by biochemical assays, that the majority of the HA molecules were in a form indistinguishable from the low-pH form of HA. The acidotropic agent, ammonium chloride, stabilized the accumulation of HA in its native form. Coexpression of HA and the homotypic influenza virus M2 protein, which has ion channel activity, stabilized the accumulation of HA in its pH neutral (native) form, and the M2 protein ion channel blocker, amantadine, prevented the rescue of HA in its native form. These data provide direct evidence that the influenza virus M2 protein ion channel activity can affect the status of the conformational form of cleaved HA during intracellular transport.